Des « conciliations par le haut » ; la pratique du ṣulḥ dans le règlement des querelles théologiques à Bagdad aux ve-vie/xie-xiie siècles - Vanessa Van Renterghem (Revue des Mondes Musulmans et de la Méditerranée)
This article presents six cases of conciliation (ṣulḥ) that took place in Baghdad between 460/1068 and 537/1142, in the context of the political domination of the Seljuq sultans over the Abbasid caliphate. These are the only cases for which detailed documentation is available among Arabic sources. While conciliation can be understood as a method for settling precedence disputes between individuals, the study shows that it also enabled the caliph to intervene in controversial and sensitive ideological issues that threatened Baghdadi public order. In some cases, conciliation was the final phase of a maẓālim procedure. Should conciliation fail, the caliph would take the final decision. Through a conclusive synthesis we examined some similarities in these cases in terms of procedure, aims, results, and political and social issues.